Analysis of Factor VIII polymorphic markers as a means for carrier detection in Brazilian families with haemophilia A - De Carvalho, F. M.; Wolfgramm, E. de Vargas; Paneto, G. G.; Careta, F. de Paula; Perrone, A. M. Spagnol; De Paula, F.; Louro, I. D. (Blackwell Publishing, 2007)
Haemophilia A is an X-linked, recessively inherited bleeding disorder of varying severity, which results from the deficiency of procoagulant factor VIII f(8). Linkage diagnosis using polymorphic markers in the f8 gene is widely used to detect carriers. The objective of this study was to verify the informativeness of three polymorphic markers in the Brazilian population, to evaluate the usefulness of such markers in carrier detection procedures. Sixty-three unrelated healthy volunteers and 10 haemophilic families were studied. Two microsatellite repeats and one HindIII RFLP markers were used. Carrier and non-carrier status could be determined in 80% of females investigated. Intron 13 markers presented the highest heterozygosity rate (79%) followed by intron 22 (68%) and intron 19 (57%). When all three markers were used together, linkage analysis informativeness increased significantly. We conclude that these markers are suitable for carrier detection in the Brazilian population and we recommend their use in combination to maximize diagnostic efficiency.
Keywords: Brazilian population; carrier detection; genetic markers; haemophilia A; linkage analysis; polymorphism